English Language Teachers’ Perceptions of Online Teaching During the Covid-19 Pandemic Period: A Case Study - Davulcu, Erbil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The fundamental goal of the present study is to explore English language teachers’ perceptions of online language learning who are working at Eastern Mediterranean University (EMU) Foreign Languages and Preparatory School (FLEPS) in TRNC. This study also investigated participants’ awareness of contemporary technologies, their perceptions of Information Communication Technology (ICT) and their attitudes regarding the use of computer technology in classroom environments. The current study is an embedded single-case study, which employs correlation analysis using descriptive statistics to identify English language teachers’ perception of online language teaching, specifically during the Covid-19 pandemic period. In this study, mixed method research was used in order to ensure triangulation, by combining both qualitative and quantitative research methods. More specifically, a Likert-based online questionnaire was conducted with 91 in-service English teachers, and face-to-face semi-structured interviews were conducted with 17 English teachers. In this study, non-probability sampling technique was used in order to select participants. More specifically, the researcher benefited from snowball sampling as well as purposive sampling methods to add new respondents who had experienced emergency remote teaching during the coronavirus pandemic period. It is observed that the perceptions of the respondents regarding ICT, computers in general and the use of computer technology in educational context, especially in classroom environments are highly positive. However, they are somewhat hesitant of online language instruction. The participants agreed that the use of computer technology in education is considered as beneficial. Furthermore, they believe that computer technology can improve the quality of the language learning and teaching. However, based on the results of the quantitative analysis, it was revealed that they do not strongly support online language teaching and learning, that is almost half of the participants (45,1%) prefer traditional face-to-face education for language instruction instead of online language teaching. Based on the qualitative data analysis, it was revealed that the sudden instructional shift from traditional education into fully online language teaching resulted in decrease of the quality of the courses delivered. Therefore, teachers believe that online courses should be prepared carefully and systematically before they are conducted. Keywords: Emergency Remote Teaching, Online Language Teaching, Distance Education, English Preparatory School, English Language, ICT, Embedded Sing-case Study, Snowball Sampling, Mixed Methods Research, Covid-19, Pandemic
Master of Arts in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2022. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: English Language Teaching (ELT) Department; English Language Teachers - English Study and Teaching - Online Teaching; Covid 19 Pandemic - English Teaching - Online Teaching; Emergency Remote Teaching, Online Language Teaching, Distance Education, English Preparatory School, English Language, ICT, Embedded Sing-case Study, Snowball Sampling, Mixed Methods Research, Covid-19, Pandemic